The Effect Of Sago Flour And Red Bean Substitution On Crysty Level and Protein Levels Of Dry Pia. - Jan Rudolf Assa; Lucy C. Mandey; Tasya V. Lagarinda (Sam Ratulangi University, 2022)
Pia is a popular snack food, the main raw material is wheat flour which is still an imported material in the form of wheat seeds. Imports of Indonesian wheat seeds tend to increase from 2010 to 2020. To reduce the use of wheat flour, especially in dry pia, it is necessary to substitute sago flour, the addition of sago flour is also related to the level of crispness. The problem is that the protein content of sago flour is low, so it is necessary to substitute red bean flour which has a high protein content. This study substituted sago flour and red bean flour with the following proportions: Wheat Flour 70%: Sago Flour 10%: Red Bean Flour 20% (T0); Wheat Flour 60%: Sago Flour 20%: Red Bean Flour 20% (T1); Wheat Flour 50%: Sago Flour 30%: Red Bean Flour 20% (T2); Wheat Flour 40%: Sago Flour 40%: Red Bean Flour 20% (T3). The results showed that protein content decreased with an increasing proportion of sago flour and dry pia crispness increased with the increasing proportion of sago flour. Keywords: Dried pia, substitution, level of crispness, protein Abstrak Pia merupakan makanan ringan yang digemari masyarakat, bahan baku utamanya adalah tepung terigu yang saat ini masih merupakan bahan import dalam bentuk biji gandum. Import biji gandum Indonesia cenderung meningkat dari tahun 2010 sampai 2020. Untuk mengurangi penggunaan tepung terigu khususnya pada pia kering perlu substitusi tepung sagu, penambahan tepung sagu juga berhubungan dengan tingkat kerenyahan. Masalahnya kadar protein tepung sagu rendah sehingga perlu juga substitusi tepung kacang merah yang kadar proteinnya tinggi. Penelitian ini melakukan substitusi tepung sagu dan kacang merah dengan proporsi: Tepung Terigu 70% : Tepung Sagu 10% : Tepung Kacang Merah 20% (T0); Tepung Terigu 60% : Tepung Sagu 20% : Tepung Kacang Merah 20% (T1); Tepung Terigu 50% : Tepung Sagu 30% : Tepung Kacang Merah 20% (T2); Tepung Terigu 40% : Tepung Sagu 40% : Tepung Kacang Merah 20% (T3). Hasil penelitian menujukkan kadar protein menurun dengan meningkatnya proporsi tepung sagu dan tingkat kerenyahan pia kering meningkat dengan bertambahnya proporsi tepung sagu. Kata kunci: Pia kering, substitusi, tingkat kerenyahan, kadar protein.